Communicative Rituals and Audiovisual Translation – Representation of Otherness in Film Subtitles - Guillot, Marie-Noëlle (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
In a contrastive study of front door rituals between friends in Australia and France (Béal and Traverso 2010), the interactional practices observed in the corpus collected are shown to exhibit distinctive verbal and non-verbal features, despite similarities. The recurrence of these features is interpreted as evidence of a link between conversational style and underlying cultural values.Like contrastive work in cross-cultural pragmatics more generally, this conclusion raises questions of representation from an audiovisual and audiovisual translation perspective: how are standard conversational routines depicted in film dialogues and in their translation in subtitling or dubbing? What are the implications of these textual representations for audiences? These questions serve as platform for the case study in this article, of greetings and other communicative rituals in a dataset of two French and one Spanish contemporary films and their subtitles in English. They are addressed from an interactional cross-cultural pragmatics perspective and draw on Fowler’s Theory of Mode (1991, 2000) to assess subtitles’ potential to mean cross-culturally as text.